2021
DOI: 10.1021/acsomega.1c06118
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Evolution Trend of the Pore Structure and the Permeability of Coal under Cyclic Loading and Unloading

Abstract: In the deep mining process of coal seams, the mechanical environment of the coal body is complex and in the state of cyclic loading and unloading. The change in the stress state leads to the change in the pore characteristics and the permeability. To investigate the effects of cyclic loading and unloading on the pore characteristics and the permeability of coal, the seepage experiment was carried out for the coal samples using the self-developed triaxial permeation instrument. By pressure confining and continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…To predict the performance characteristics of reservoirs, it is necessary to model the changes in permeability during cyclic filling and emptying. To achieve this, rock samples are tested under laboratory conditions using cyclic confining pressure to simulate variations in pore pressure (Yang and Hu, 2018;Lei et al, 2020;Liu et al, 2020;Xin et al, 2021;Wang et al, 2022;Kozhevnikov et al, 2023). Numerous experimental studies have observed that the curves depicting the reduction and restoration of permeability under loading are most accurately represented by power law functions (Li et al, 2014;Zheng et al, 2015;Milsch et al, 2016;Nolte et al, 2021;Stanton-Yonge et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…To predict the performance characteristics of reservoirs, it is necessary to model the changes in permeability during cyclic filling and emptying. To achieve this, rock samples are tested under laboratory conditions using cyclic confining pressure to simulate variations in pore pressure (Yang and Hu, 2018;Lei et al, 2020;Liu et al, 2020;Xin et al, 2021;Wang et al, 2022;Kozhevnikov et al, 2023). Numerous experimental studies have observed that the curves depicting the reduction and restoration of permeability under loading are most accurately represented by power law functions (Li et al, 2014;Zheng et al, 2015;Milsch et al, 2016;Nolte et al, 2021;Stanton-Yonge et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The fatigue failure patterns of water‐bearing sandstone under cyclic loading were investigated with various amplitude levels and loading frequencies based on the numerical simulation method 12 . Xin et al 13 studied the porosity and permeability of coal with different cyclic paths. Peng et al 14 analyzed the energy dissipation and crack propagation modes of fractured sandstone with different cyclic gradient loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, according to Refs. [ [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] ], the decrease in permeability of porous rocks (sandstones, coal and limestones) under cyclic loading results only in the closure of micropores and cracks. The authors ignore colloid migration even though the permeability is measured with the obligatory injection of gases and liquids regardless of the measurement method in a steady state or pulse decay method.…”
Section: Introductionmentioning
confidence: 99%